Economic MPC with a contractive constraint for nonlinear systems. (25th April 2016) - He, Defeng; Sun, Jing; Yu, Li
Summary: In this paper, we consider the stability issue of economic model predictive control (EMPC) for constrained nonlinear systems and propose a new contractive constraint formulation of nonlinear EMPC schemes. This formulation is one of Lyapunov‐based approaches in which the contractive function chosen a priori can be used as a Lyapunov function. Some conditions are given to guarantee recursive feasibility and asymptotic stability of the EMPC. Moreover, we analyze the transient economic performance of the EMPC closed‐loop system in some finite‐time intervals. The proposed EMPC scheme is applied to a chemical reactor model to illustrate its utility and benefits. Copyright © 2016 John Wiley & Sons, Ltd.